Reduction of dilution error in ELISAs using an internal standard. (July 2016) - Verch, Thorsten; Roselle, Christopher; Shank-Retzlaff, Mary
Background: Dilution bias is a major cause of immunoassay variability due to the lack of an internal standard to determine the true versus the expected dilution value.Methodology: We used an internal control to measure dilution bias in an ELISA. Acridine-orange was added at the first dilution step and monitored throughout dilutions. Assay results were corrected using the fluorescent signal ratio between samples and reference. Acridine dilution correlated with analyte-specific assay measurements (R2 = 0.987). Correction of assay results with the measured dilution factor improved both accuracy and precision resulting in a reduction of >50% %CV reduction.Conclusion: Dilution correction can significantly improve accuracy and precision of immunoassays. Additional control strategies may further mitigate other sources of variability.